2022
DOI: 10.1002/ptr.7448
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on clinical evidence of the efficacy of lavender in sleep disorders

Abstract: Sleep disorders are one of the most prevalent psychiatric diseases. Insomnia is the most common sleep disorder amongst the general population. It is also one of the most frequent complaints in primary healthcare centers. Lavender is called "the broom of the brain" in different oriental traditional medicines. It is one of the most used plants for patients with sleep disorders. This study reviews what is currently known about the use of lavender for sleep disorders in patients with different diseases, from cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Regarding the effectiveness of lavender for therapeutic purposes, research is inconclusive [ 43 ]. However, recent reviews summarize promising evidence for lavender use against sleeping disorders [ 44 , 45 ]. Empirical research on the efficacy of lavender against neuropathic pain is limited; however, basic research on mice [ 46 ] and in patients with diabetes [ 47 ] has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effectiveness of lavender for therapeutic purposes, research is inconclusive [ 43 ]. However, recent reviews summarize promising evidence for lavender use against sleeping disorders [ 44 , 45 ]. Empirical research on the efficacy of lavender against neuropathic pain is limited; however, basic research on mice [ 46 ] and in patients with diabetes [ 47 ] has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…[121] Techniques are crucial in improving stability, shelf life, and bioavailability of bioactive valuable compounds. Encapsulation systems, including SD, coacervation, emulsification, encapsulation in lipid carriers, and sol-gel encapsulation, have been developed to address the challenges associated with the volatile and sensitive nature of these compounds [122][123][124][125][126][127][128] Each encapsulation technique has distinct advantages and disadvantages, which determine its suitability for specific applications. SD is a commonly used and economical process, generating particles with a narrow size distribution; however, it may lead to reduced bioactivity due to exposure to high temperatures.…”
Section: Encapsulation In Lipid Carriersmentioning
confidence: 99%
“…Techniques are crucial in improving stability, shelf life, and bioavailability of bioactive valuable compounds. Encapsulation systems, including SD, coacervation, emulsification, encapsulation in lipid carriers, and sol‐gel encapsulation, have been developed to address the challenges associated with the volatile and sensitive nature of these compounds [122–128] …”
Section: Systems Used In the Encapsulationmentioning
confidence: 99%
“… 9 , 10 Several recent studies indicate that patients with various diseases have explored clinical applications involving different dietary supplements and complementary medicine. 11 , 12 , 13 Therefore, many patients may adopt complementary and alternative medications (CAM) to achieve their individual desires.…”
Section: Introductionmentioning
confidence: 99%